2015
DOI: 10.3109/0886022x.2014.996109
|View full text |Cite
|
Sign up to set email alerts
|

Factors limiting usefulness of serum and urinary NGAL as a marker of acute kidney injury in preterm newborns

Abstract: Background: Neutrophil gelatinase-associated lipocalin (NGAL) is postulated to be a highly sensitive and specific marker of acute kidney injury (AKI). The aim of this study was to assess the factors affecting serum and urine total NGAL in preterm newborns, limiting the role of this new potential marker of AKI. Methods: Serum and urinary total NGAL concentrations were determined in 57 preterm infants admitted to the Neonatal Intensive Care Unit in the following points of time: first week of life, between 8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…17 Furthermore, according to Askenazi et al, 10 uNGAL/mgCr also decreases with increasing GA, and there are detailed reports where uNGAL levels declined by 23.1% 10 or by 17.8% 17 for each week of increasing GA. However, there are also researchers who found no association between uNGAL and GA 23,25,30,39 and those who report no correlation with BW, 23,30,39 or PNA. 23,27,38 However, Huynh et al 17 demonstrated that uNGAL levels declined by 1.33% for each day of PNA.…”
Section: Discussionmentioning
confidence: 98%
“…17 Furthermore, according to Askenazi et al, 10 uNGAL/mgCr also decreases with increasing GA, and there are detailed reports where uNGAL levels declined by 23.1% 10 or by 17.8% 17 for each week of increasing GA. However, there are also researchers who found no association between uNGAL and GA 23,25,30,39 and those who report no correlation with BW, 23,30,39 or PNA. 23,27,38 However, Huynh et al 17 demonstrated that uNGAL levels declined by 1.33% for each day of PNA.…”
Section: Discussionmentioning
confidence: 98%
“…Pertinently to PE, it is also well established as an early biomarker of acute kidney injury (AKI) (838841). However, it is not a specific biomarker for AKI vs. sepsis (839, 842850) and its origin in sepsis differs (851, 852). Of course, it can be the sepsis that leads to the AKI (853, 854).…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%
“…Prior literature has shown that in premature infants without AKI, urine proteins will be highest among those with the lowest GA, probably because of the passive loss of proteins in the context of immature tubular function (6)(7)(8). Previously, we (7) and others (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have published data on the ability of urine biomarkers to predict AKI in neonates; however, these studies are limited by the size of the cohort or the use of nested case-control methods, with most of these studies evaluating only one biomarker. In addition, previous studies were subject to risk of misclassification bias, given that many infants had only a few SCr levels measured to determine AKI.…”
Section: Introductionmentioning
confidence: 99%